Ecophysiology of seed germination in Digitaria insularis ((L.) Fedde) - Mendonça, Giovana; Martins, Cibele; Martins, Dagoberto; Costa, Neumárcio (Revista Ciência Agronômica, 2014)
The invasive behaviour of sourgrass (Digitaria insularis) in cultivated areas is due to its strategy of aggressive regeneration, which is based on seed germination. Knowledge of the physiological ecology of this species can contribute to the development of management and control strategies. The aim of this research was to understand the effects of provenance, temperature and light on the germination of sourgrass seeds collected in the Brazilian state of São Paulo in the cities of Americana, Botucatu and São José do Rio Preto and in the state of Paraná in the city of São Miguel do Iguaçu. The seeds were left to germinate at temperatures of 15, 25, 35 and 45 °C, both with and without light. The number of normal seedlings was recorded daily from seven to 60 days. After this period, the seeds together with substrate, were transferred to 25 oC with light, and a daily count was made for all treatments until the end of germination (75 days after sowing). The seeds of D. insularis are positively photoblastic. Seed germination in this species depends on provenance. A temperature of 4 5 °C for germination is lethal to the seeds. The temperature of 35 °C in the presence of light is the most favourable condition for seed germination.